Navigating the E-Commerce Temptation: an In-Depth Analysis of Impulse Buying in Shopee with Inflation as a Moderator - Irma Nina Fauziah Ritonga; Satria Tirtayasa (Jurnal Bisnis dan Manajemen, 2023)
The purpose of this study was to systematically analyze the influence of Hedonic Shopping Motivation, Brand Image, and Fashion Involvement on Impulse Buying behavior within the context of Shopee e-commerce. Moreover, this research aimed to assess the moderating role of Inflation as a crucial variable in shaping the relationships. To achieve this, the study employed a population determined by the Lemeshow formula, resulting in a sample size of 384 respondents selected through purposive sampling. Data collection was conducted via an online questionnaire distributed through Google Forms. Hypothesis testing was carried out using established statistical methods, including tests for classical assumptions, multiple regression analysis, and hypothesis testing with the aid of SPSS software. The findings of this study revealed significant relationships between the individual factors of Hedonic Shopping Motivation, Brand Image, and Fashion Involvement with Impulse Buying. Notably, Hedonic Shopping Motivation and Brand Image displayed significant effects on Impulse Buying behavior. Additionally, the research discerned that Inflation acted as a moderator, significantly influencing the relationship between Hedonic Shopping Motivation and Impulse Buying. However, Inflation did not exhibit a moderating effect on the relationship between Brand Image and Impulse Buying. These results contribute to a deeper understanding of consumer behavior dynamics within the Shopee e-commerce platform, offering valuable insights for both academic discourse and practical implications in the realm of online retailing.